- 1-800-665-6601
- [email protected]

Dividing the given two fractions, the expression looks like this (3/2) / (6/10)

The first fraction is ‘3/2’ and the second fraction placed below is ‘6/10’.

In order to divide two fractions, the second fraction is flipped upside down.

This 10/6 is multiplied with the first fraction 3/2.

(3/2) * (10/6) -> (3 * 10)/ (2 *6)

30/12 -> this is simplified to 5/2.

Dividing the given two fractions, the expression looks like this -> (5/8) / (1/2)

The first fraction is ‘5/8’ and the second fraction placed below is ‘1/2’.

In order to divide two fractions, the second fraction is flipped upside down.

This 2/1 is multiplied with the first fraction 5/8.

(5/8) * (2/1) -> (5 * 2)/ (8 * 1)

10/8 -> this is simplified to 5/4.